Disign SPWM multilevel inverter single phase15 level - Effendi Effendi; Ira Devi Sara; Rakhmad Syafutra Lubis (Universitas Syiah Kuala, 2016)
Fifteen level single phase multilevel inverter is constructed using power circuit consist of 7 MOSFETs, seven independents DC sources, seven diodes, and an H-Bridge circuit. Switching method used in this MLI is sinusoidal pulse width modulation (SPWM) multicarrier where the reference wave in the form of a sinusoidal wave. Multicarrier SPWM circuit is designed using electronic components such as Op-Amp that used as a comparator and some logic gates such as AND, OR and NOT gate to trigger S1, S2, S3, S4, S5, S6, S7, and H-Bridge circuit. Carrier waves used in this MLI modified from the triangle wave that having a frequency into carrier waves without frequency (DC sources) where THD that generated into 5.502%. While methods that use frequency such as Phase Disposition PWM (PD PWM), Phase Shift PWM (PS-PWM), and Carrier Overlapping PWM (CO PWM) that produces THD greater than the proposed method, this system was simulated using PSIM software.